ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING LOAN DENGAN BANK SIZE, SIZE OF AUDIT FIRM, PERTUMBUHAN GDP SEBAGAI VARIABEL KONTROL (Studi pada Bank Konvensional di Bursa Efek Indonesia Periode 2013-2017) - Wulandari, Putri Sekar; Demi Pengestuti, Irene Rini Demi (Faculty of Economics and Business Diponegoro University, 2018)
This research aims to analyze the influence of Institutional Ownership, Board Size, BOPO, and Loan to Deposit Ratio to credit risk that measured by Non Performing Loan with Bank Size, Size of Audit Firm and GDP Growth as a control variabels.The population of this research is the conventional banks listed on the Indonesia Stock Exchange in the 2013-2017 period. The sampling technique used is purposive sampling so that the samples obtained were 24, data were obtained from the bank's annual report. The analytical method used is Ordinary Least Square which consists of statistical f test, statistical t test, coefficient of determination () test and the classic assumption test which includes normality test, multicollinearity test, autocorrelation test and heteroscedasticity test.The results showed that Institutional Ownership had no effect on Non-Performing Loans, the Board Size had a negative effect on Non-Performing Loans, BOPO had a positive effect on Non-Performing Loans, Loan to Deposit Ratio had a positive effect on Non-Performing Loans. Regression estimation results show the ability to predict the model by 29.7%, while the remaining 70.3% is influenced by other factors outside the model.